Comparison Between Alfuzosin Monotherapy And Combination of Alfuzosin With Finasteride In Symptomatic Benign Prostatic Hyperplasia - Siddique, Md Saifuddin Ahmed; Bashar, Sharmin Nahar; Haque, Mohammed Monowar UL; Latif, Md Abdul; Ahmed, Farid Uddin (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background: Lower Urinary Tract Symptoms (LUTS) due to Benign Prostatic Hyperplasia (BPH) are common in elder men and a number of drugs alone or combined are clinically used for this disorder. This study was aimed to evaluate the efficacy and safety of Alfuzosin monotherapy versus combination of Alfuzosin and Finasteride in treatment of LUTS due to BPH. Materials and methods: This clinical trial was conducted in the outpatient Department of Urology Chittagong Medical College Hospital from May 2007 to October 2008. After assessing for the eligibility, consecutive consenting 60 patients with LUTS related to BPH were randomly assigned to either 10mg Alfuzosin (Group A) or combination of 10mg Alfuzosin and 5mg Finasteride (Group B) for 12 months. The response was assessed by measurements of International Prostate Symptoms Score (IPSS) Maximum urine flow rate (Qmax), Post Voidal Residual Volume (PVR) and prostate volume at baseline and 3 monthly thereafter. Safety was assessed by Adverse Drug Events (ADE) rate. Results: Both Groups showed comparable significant improvements in all parameters in terms of decreasing IPSS, PVR and increasing Qmax. Both treatments were well tolerated with respect to ADE and distribution of ADE was similar in two groups. Conclusion: In men with benign prostatic hyperplasia, Alfuzosin was effective therapy and the combination of Alfuzosin and Finasteride was no more effective than Alfuzosin alone. JCMCTA 2017 ; 28 (2) : 75-80